A study of the speech act of complaining / Nurfarahin Ahmad, Nalini Arumugam and Kaarthiyaini Supramaniam - Ahmad, Nurfarahin; Arumugam, Nalini; Supramaniam, Kaarthiyaini (Universiti Teknologi MARA Shah Alam, 2017)
The present study aims to examine the speech act of complaining performed by consumers of a particular organisation by investigating the pragmatics strategies employed by the consumers in complaining. The behaviours of Malaysian non-native English speakers when making online complaints directed to an organisation is expected to have different approaches and preferences compared to complaints produced by native speakers of English. A case study approach was used in this qualitative study to investigate the preference of Malaysian non-native speakers of English language when making online complaints with respect to the components of the speech act set of complaining by analysing 50 online complaints, posted by 50 customers via www.complaintsboard.com. The results indicated that the component of complaining is found to be the most frequent in online complaints. Besides, it was also found that the complaints made by non-native speakers did not appear in isolation but accompanied by other components of speech act like criticism, justification, request for explanation, warning and threat and sarcasm. In addition, Malaysian non-native English speakers employed complaint strategy that lies under the third level of severity of complaint which means they produced the complaint by expressing it explicitly.